Development of thermal electric cooling air conditioner by evaporative cooling - Abd Aziz, Muhammad Syahril (2021)
A small private office space usually has a low cooling load. It would consume excess energy when a compressor-based air conditioner is used to provide a thermal comfort zone as outlined by the American Society of Heating, Refrigerating and Air-Conditioning Engineers thermal comfort standard (ASHRAE-55). It has been calculated that a lot of wastage and inefficiencies would occur in using such a compressor-based unit for the low load office space. Hence, the aim of this study is to develop a small type air conditioner that utilises thermal electric cooling (TEC) to overcome the weaknesses of a compressor-based unit. Therefore, the main approach is to design several concepts of the TEC air conditioner by evaporative cooling and select the best design, fabricate the selected design and evaluate the performance of the developed product. In the synthesis stage, the House of Quality (HOQ) method was used to identify project’s needs by gathering the engineering requirements. Morphological chart was then used as a tool to generate various concepts from each engineering criterion. Finally, the Pugh’s selection method was applied to select the best concept. The selected design was fabricated by following the schematic diagram to ensure the developed product can function well. Next, various engineering performance criteria were evaluated for the system such as the Coefficient of Performance (COP) of the TEC plate, the COP of the developed product, the COP of evaporative cooler and the sound level of the product. The test area size of the office was 12 ft × 11 ft, which was used for light activities and with few equipment that generates heat. As a result, after going through some design concepts generated by using the design tools, the TEC air conditioner by evaporative cooling was finally developed which consists of several parts such as the thermoelectric modules model TEC-12706, a heat sink fan, a water heat sink, a water pump, water pipelines, a radiator and an evaporative cooler. The performance results show that this system is capable to increase the COP of the TEC plates from previous studies that used various condensing methods. This experiment found that the COP of the TEC plates condensed by evaporative cooling was 0.39. The optimum running current for the system was 5 A when the system’s COP achieved the highest values, which was 1.7. However, the COP of the evaporative cooling decreased with the increment of the current supply to the TEC. Subsequently, the 62.9 dB sound level of the system is acceptable by comparing it to the sound level standard.